Self-reported dietary flavonoid intake and serum markers of inflammation: The Multiethnic Cohort - Rohrmann, Sabine (Cancer Causes Control, 2018)
PURPOSE: To examine if dietary intake of foods rich in flavonoids, which have been shown to be inversely associated with chronic diseases, is associated with inflammatory processes. METHODS: This analysis includes controls of case-control studies nested within the Multiethnic Cohort (MEC) who completed a validated food frequency questionnaire at cohort entry. Biomarkers were assessed in blood donated during follow-up (mean=9.6 years). We used multivariate linear regression adjusted for potential confounders to estimate associations between intake of flavanones, flavonols, and isoflavones and levels of adiponectin, leptin, C-reactive protein, interleukin (IL)-1β, IL-6, IL-10 and tumor necrosis factor-α. RESULTS: Among the 1,287 participants, the respective median intakes of flavanones, flavonols, and isoflavones were 26.5, 12.4, and 1.3 mg/day at cohort entry. With the exception of flavanone intake, which was statistically significantly inversely associated with adiponectin (p=0.01) and IL-6 concentrations (p=0.01), none of the examined flavonoids was related with levels of adipokines or inflammatory markers. Heterogeneity by ethnicity was only observed for flavonol intake and IL-10 (p(interaction)=0.04) and may be the result of multiple testing. These null findings were confirmed in a subset of participants who completed a second dietary history within 2.6 years of blood draw. CONCLUSION: The current results do not support a consistent association between dietary intake of flavonoids and markers of inflammatory processes.